Report ranks U.S. coastal state protection of marine areas. (11th June 2013) - Showstack, Randy
Abstract : Most U.S. coastal states are not doing enough to safeguard nearby marine areas, according to a 29 May report by two environmental groups, the Marine Conservation Institute (MCI) and Mission Blue. The groups ranked U.S. coastal states and territories based on the percentage of state marine waters classified as no‐take marine protected areas (MPAs) where fishing, mining, and oil and gas development are not allowed.